Economic values contained in the book of Al-Hikam ibn Athaillah as-Sakandari - Yayuli Yayuli; Ahmad Yusuf Efendi; Muhamad Subhi Apriantoro; Al Milla Hamidah; Rozi Irfan Rosyadhi (Global Research Network, 2024)
This study aims to learn more about the Economic Values in Ibn Athaillah As-Sakandari's Kitab Al-Hikam. In this study, the author used qualitative methods. Based on researchers' findings in the book of Al-Hikam by Ibn Athaillah As-sakandari, six points discuss economic values, namely a). Worship and Business must be Balanced; b). The extinguishing of the eyes of the heart, c). Different practices, d). Stay active about world affairs, e). infaq, f). Obedience is a gift of Allah Swt. From these six points, it can be concluded that the book can be taken as Wisdom regarding how to obtain the sustenance of Allah Almighty, where we are encouraged to pray and try to seek care because the reality has always been that the crowd is too focused on pursuing the world so that they forget the end and vice versa.